Fair and unfair income inequalities in Europe - Daniele Checchi; Vito Peragine; Laura Serlenga (Institute for the Study of Labor (IZA), 2010)
This paper analyses the extent of income inequality and opportunity inequality in 25 European countries. The present work contributes to understanding the origin of standard income inequality, helping to identify potential institutional setups that are associated to opportunity inequality. We distinguish between ex ante and ex post opportunity inequality. We find that ex ante equality of opportunity exhibits positive correlation with public expenditure in education, whereas ex post equality of opportunity is also positively associated to union presence and to fiscal redistribution.
Keywords: D31; D63; J62; 330; Inequality of opportunity; income inequality; Einkommensverteilung; Bildungschancen; Gerechtigkeit; Schätzung; Westeuropa